2014
DOI: 10.1007/s12272-014-0478-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents of Triticum aestivum and their effects on adipogenic differentiation of 3T3-L1 preadipocytes

Abstract: In this report, we investigated the anti-obesity effect of wheat sprouts and their component compounds. Twenty compounds (1-20) were isolated from Triticum aestivum. Among them, glycolipids 1-5 were determined for the first time from T. aestivum and its sprouts. The HPLC analysis demonstrated that compounds 1-3, 5, 8, 12, and 14 were major peak in the HPLC chromatogram of the active fraction. The effects of the compounds on lipid accumulation were assessed at concentrations ranging from 1.0 to 100 μM. At conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Wheat ARs have been revealed to play an important role in the prevention of cancers79, diabetes80, and CVD80. Similarly, cereal BXs showed cytotoxic effects81, and could also significantly decrease lipid accumulation in 3T3-L1 preadipocytes82. In addition to the direct radical scavenging activity8384, simple phenolic acids, such as ferulic acid, caffeic acid, gallic acid, and cinnamic acid, possess antidiabetic properties85.…”
Section: Discussionmentioning
confidence: 99%
“…Wheat ARs have been revealed to play an important role in the prevention of cancers79, diabetes80, and CVD80. Similarly, cereal BXs showed cytotoxic effects81, and could also significantly decrease lipid accumulation in 3T3-L1 preadipocytes82. In addition to the direct radical scavenging activity8384, simple phenolic acids, such as ferulic acid, caffeic acid, gallic acid, and cinnamic acid, possess antidiabetic properties85.…”
Section: Discussionmentioning
confidence: 99%
“…Extraction and purification of triticumoside from TA Triticumoside was prepared as previously described [10,12]. Briefly, methanol extract of TA sprouts was partitioned with n-hexane, dichloromethane (CH 2 Cl 2 ), ethyl acetate (EtOAc), and n-BuOH to give hexane extract, CH 2 Cl 2 extract, EtOAc extract, BuOH extract, and water layer, respectively.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…Previous reports have indicated that extract of TA has antidiabetic, antihyperlipidemic, and anticancer effects [4][5][6][7][8][9]. Moreover, TA extract is known to contain several phytocompounds such as leuteolin, isoscoparin, isoorientin, and triticumoside [10][11][12]. However, there have not yet been any studies on the effects and potential mechanisms of anticancer effects of compounds isolated from TA, until now.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown phenolic compounds and vitamins synthesized during the sprouting of wheat grass have potent antioxidant and antiinflammatory properties (Benedetti et al, ; Luyen et al, ; Mohan et al, ). In addition, it was also reported recently that a constituent of wheatgrass has anti‐obesity effects (Im et al, ; Luyen et al, ; Poudel et al, ). Furthermore, polysaccharide isolated from wheatgrass was found to reduce blood glucose level in streptozotocin (STZ)‐induced diabetic mice (Mohan et al, ) and has a stimulatory effect on insulin response (Lee et al, ).…”
Section: Introductionmentioning
confidence: 79%
“…Previous studies have shown that the antioxidant and antiinflammatory properties of wheatgrass constituents are due to the inhibition of NF‐κB activation (Poudel et al, ; Lee et al, ). Several studies have described the anti‐obesity and anti‐diabetic effects of wheatgrass (Luyen et al, ; Lee et al, ). However, the effect of WGP on LPS‐induced liver injury has not been previously studied.…”
Section: Discussionmentioning
confidence: 99%